Interleucina-6 : ¿amiga o enemiga? Bases para comprender su utilidad como objetivo terapéutico (2011)
ABSTRACT: Cytokines are intercellular communication molecules. They exhibit a great range of actions in different systems and organic processes, notably in the mechanisms that produce the inflammatory response. Interleukin-6 is a pleiotropic cytokine with both pro-inflammatory and anti-inflammatory functions. Evidence links this cytokine in an important and direct way with the pathophysiology of diverse autoimmune diseases, in particular, rheumatoid arthritis. This is a review of the molecular basis and the biological effects of interleukin-6. The clinical experience accumulated with therapies that block its pro-inflammatory actions in patients with rheumatoid arthritis are also included.